Retentir: A poetics of the railway station. (1st September 2016) - Wright, Laurence Stuart
ABSTRACT: This article explores a poetics of the railway station, focused mainly on South African examples, to show how the experience of railway travel can yield moments of enhanced being, sometimes captured in poems. Referencing philosophical insights from Henri Bergson and Gaston Bachelard, the piece suggests that railway stations deliver psycho-physical experiences hospitable to the compelling images poets occasionally develop from them. Of particular importance is the quality of Minkowskian retentir (reverberation), which nudges railway station images away from the older Romantic opposition between "going" and "being" towards the multiple, shimmering, trans-historical equivocations characteristic of modernity.